Spectrum of cutaneous adverse reactions to aromatic antiepileptic drugs and human leukocyte antigen genotypes in Thai patients and meta-analysis - Sukasem, Chonlaphat; Sririttha, Suthida; Chaichan, Chonlawat; Nakkrut, Thapanat; Satapornpong, Patompong; Jaruthamsophon, Kanoot; Jantararoungtong, Thawinee; Koomdee, Napatrupron; Medhasi, Sadeep; Oo-Puthinan, Sarawut; Rerkpattanapipat, Ticha; Klaewsongkram, Jettanong; et al. (The pharmacogenomics journal, 2021)
Aromatic antiepileptic drugs (AEDs)-induced cutaneous adverse drug reactions (cADRs) add up to the limited use of the AEDs in the treatment and prevention of seizures. Human leukocyte antigen-B ( HLA-B ) alleles have been linked to AEDs-induced cADRs. We investigated the association between cADRs (including Stevens–Johnson syndrome; SJS/toxic epidermal necrolysis; TEN, drug reaction with eosinophilia and systemic symptoms; DRESS, and Maculopapular eruption; MPE) caused by AEDs (phenytoin, carbamazepine, lamotrigine, phenobarbital and oxcarbazepine) and HLA-B alleles in Thai population. Through the case-control study, 166 patients with AEDs-induced cADRs, 426 AEDs-tolerant patients (AEDs-tolerant controls), and 470 healthy subjects (Thai population) were collected. The HLA genotypes were detected using the polymerase chain reaction-sequence specific oligonucleotide probe (PCR-SSOP) method. We also performed a meta-analysis with these data and other populations. The carrier rate of HLA-B*15:02 was significantly different between AEDs-induced cADRs group and AEDs-tolerant group (Odds ratio; OR 4.28, 95% Confidence interval; CI 2.64–6.95, p < 0.001), AEDs-induced cADRs group and Thai population (OR 2.15, 95%CI 1.41–3.29, p < 0.001). In meta-analysis showed the strong association HLA-B*15:02 with AEDs-induced cADRs (OR 4.77, 95%CI 1.79–12.73, p < 0.001). Furthermore, HLA-B*15:02 was associated with SJS/TEN induced by AEDs (OR 10.28, 95%CI 6.50–16.28, p < 0.001) Phenytoin (OR 4.12, 95%CI 1.77–9.59, p = 0.001) and carbamazepine (OR 137.69, 95%CI 50.97–371.98, p < 0.001). This study demonstrated that genetic association for AEDs-induced cADRs was phenotype-specific. A strong association between HLA-B*15:02 and AEDs-induced SJS/TEN was demonstrated with an OR of 10.79 (95%CI 5.50–21.16, p < 0.001) when compared with AEDs-tolerant group. On the other hand, the carrier rates of HLA-B*08:01 , HLA-B*13:01 , and HLA-B*56:02 were significantly higher in the DRESS group compared with the AEDs-tolerant group ( p = 0.029, 0.007, and 0.017, respectively). The HLA-B*15:02 allele may represent a risk factor for AEDs-induced cADRs.